2019
DOI: 10.1039/c8cy02331j
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of nucleophilic catalysis with proton transfer in the nitrile reductase QueF from Escherichia coli

Abstract: Proton relay through an active-site network of hydrogen bonds promotes enzymatic nitrile reduction to amine via a covalent thioimidate enzyme intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Single‐site variants of ecQueF (C190A, C190S, D197A, D197H) were isolated and characterized for activity in preQ 0 reduction, along with the wild‐type enzyme . Catalytic reactions of the variants with preQ 0 were peculiar in that their NADPH consumption greatly exceeded the corresponding preQ 1 release, and the excess utilization of NADPH was largely uncoupled from the formation of NADP + .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single‐site variants of ecQueF (C190A, C190S, D197A, D197H) were isolated and characterized for activity in preQ 0 reduction, along with the wild‐type enzyme . Catalytic reactions of the variants with preQ 0 were peculiar in that their NADPH consumption greatly exceeded the corresponding preQ 1 release, and the excess utilization of NADPH was largely uncoupled from the formation of NADP + .…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism of QueF catalysis involves a thioimidate covalent enzyme‐preQ 0 adduct that undergoes reduction by NADPH in two catalytic steps via an imine intermediate (Scheme ) . The QueF active site consists of a cysteine/aspartate dyad of residues that operate in a functionally interconnected manner in covalent enzyme catalysis, as shown in Scheme . As part of our investigation of the QueF mechanism, we substituted the relevant Cys190 (by Ala and Ser) and Asp197 (by Ala and His) in the enzyme from Escherichia coli (ecQueF) and studied preQ 0 reduction in the presence of the enzyme variants .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26] Many biological processes like enzyme catalysis rely on nucleophiles formed by proton transfer reactions. [27][28][29] For example, the self-cleavage mechanism in hairpin ribosomes proceeds via proton transfer involving internal nucleophiles. 30 Moreover, Neves et al 19 reported nucleophilic disulfide bond rupture by the proton transfer mechanism in Protein Disulfide Isomerase (PDI), the mammalian counterpart of nDsbD.…”
Section: Introductionmentioning
confidence: 99%